Investments in education and welfare in a two-sector, random matching economy - Concetta Mendolicchio; Dimitri Paolini; Tito Pietra (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2011)
We consider a random matching model where heterogeneous agents choose optimally to invest time and real resources in education. Generically, there is a steady state equilibrium, where some agents, but not all of them, invest. Regular steady state equilibria are constrained inefficient in a strong sense. The Hosios (1990) condition is neither necessary, nor sufficient, for constrained efficiency. We also provide restrictions on the fundamentals sufficient to guarantee that equilibria are characterized by overeducation (or undereducation), present some results on their comparative statics properties, and discuss the nature of welfare improving policies. – – Im Rahmen eines Matching-Modells wird die optimale Investitionsentscheidung heterogener Agenten in Humankapital untersucht. Generisch existiert ein Gleichgewicht, in dem einige, aber nicht alle Agenten investieren. Reguläre Steady-State-Gleichgewichte sind im starken Sinne beschränkt ineffzient. Die Hosios-Bedingung ist für beschränkte Effzienz weder notwendig noch hinreichend. Weiter zeigen wir Restriktionen auf, die hinreichend sind für die Existenz eines Gleichgewichts, das durch Über- oder Unterinvestition in Bildung gekennzeichnet ist. Schließlich diskutieren wir komparativ-statische Eigenschaften des Modells sowie wohlfahrtssteigernde Politikmaßnahmen.
Keywords: J24; H2; 330; Human capital; Efficiency; Labour Supply; Bildungsinvestition; Arbeitsangebot; Matching; Wirtschaftliche Effizienz; Wohlfahrtseffekt; Mehr-Sektoren-Modell; Theorie